Ang Maging Artista sa Panahon ng Digma - Yraola, Dayang (Likhaan: The Journal of Contemporary Philippine Literature; Vol 15 No 3 (2021): Dx Machina: Literature in the Time of COVID-19 #4, 2022)
See PDF.